Peran Guru Agama Katolik Dalam Penanaman Nilai Kristiani Di Sekolah Menengah Atas Sekecamatan Sekadau Hulu - Kornelius Meiji; Tinenti, Hemma Gregorius; Yusi Kurniati (Sepakat : Jurnal Pastoral Kateketik, 2025)
The issue in this research is the lack of quality in learning, including in Catholic religious education. This certainly affects the instillation of values, which is the primary goal of learning. Therefore, the demand for teachers to become more professional is a key requirement. This study examines the role of Catholic Religious Education teachers in instilling Christian values. The research method used is qualitative, employing interview and documentation techniques to collect data. The data analysis technique for interview results involves reducing interview data, analyzing the results, and drawing conclusions. The interview process was conducted with Catholic religion teachers and students in three schools. This research was carried out in Sekadau Hulu District, involving three senior high schools in the district. The findings show that Catholic Religious Education teachers have not fully made the instillation of Christian values the primary goal of learning. The learning process tends to be merely formal, causing students to engage in it only as a graduation requirement. Teachers' preoccupation with administrative tasks also impacts the meaningfulness of the learning experience. The role of Catholic Religious Education teachers has not been maximized; learning is primarily a transfer of knowledge, and the practical activities carried out appear to have little meaningful impact on students.